Low-latitude zooplankton pigmentation plasticity in response to multiple threats. Issue 7 (24th July 2019) - Lee, Marcus; Zhang, Huan; Sha, Yongcui; Hegg, Alexander; Ugge, Gustaf Ekelund; Vinterstare, Jerker; Škerlep, Martin; Pärssinen, Varpu; Herzog, Simon David; Björnerås, Caroline; Gollnisch, Raphael; Johansson, Emma; et al.
Abstract : Crustacean copepods in high-latitude lakes frequently alter their pigmentation facultatively to defend themselves against prevailing threats, such as solar ultraviolet radiation (UVR) and visually oriented predators. Strong seasonality in those environments promotes phenotypic plasticity. To date, no one has investigated whether low-latitude copepods, experiencing continuous stress from UVR and predation threats, exhibit similar inducible defences. We here investigated the pigmentation levels of Bahamian 'blue hole' copepods, addressing this deficit. Examining several populations varying in predation risk, we found the lowest levels of pigmentation in the population experiencing the highest predation pressure. In a laboratory experiment, we found that, in contrast with our predictions, copepods from these relatively constant environments did show some changes in pigmentation subsequent to the removal of UVR; however, exposure to water from different predation regimes induced minor and idiosyncratic pigmentation change. Our findings suggest that low-latitude zooplankton in inland environments may exhibit reduced, but non-zero, levels of phenotypic plasticity compared with their high-latitude counterparts.